Background stabilization and debris flagging in launch pad videos - Gopalan, Kaushik; Kasparis, Takis (My University, 2007)
Launch pads have many cameras that record footage of the space vehicles and the surrounding areas during launches. The footage from many of these cameras is not stable due to camera vibration during ignition and lift-off from the rocket thrust. Aside from making the footage difficult to watch, these instabilities in the background make it harder for viewers to notice any debris that may have fallen from the vehicle, or any other foreign objects. In this paper, we present a method for the automatic stabilization and detection of any debris from such footage. We first stabilize the background by registering consecutive frames and subsequently detect and track moving objects that could be potentially dangerous debris.
Keywords: Cameras; Image acquisition; Launching; Spacecraft; Target tracking; Vibrations (mechanical)